Whole genome microarray data of chronic wound debridement prior to application of dermal skin substitutes. Issue 5 (2nd August 2016) - Ashrafi, Mohammed; Sebastian, Anil; Shih, Barbara; Greaves, Nicholas; Alonso‐Rasgado, Teresa; Baguneid, Mohamed; Bayat, Ardeshir
Abstract: Clinical consensus is that debridement is necessary for successful application of dermal skin substitutes (DSS) to chronic wounds. The aim here was to identify commonly expressed genes associated with wound healing in untreated acute wounds and chronic wounds treated with wound debridement followed by DSS. Cutaneous biopsies were taken at two time points from untreated acute and chronic wounds and from chronic wounds treated with DSS following debridement. Microarray analysis identified significant differences ( p  < 0.05) related to proliferation (HIPK2, LGR4, FGFR1, SRRT), migration (RHOC, PRPF40A, FGFR1), differentiation (TCF4, COL13A1, GNPTAB, HUWE1, FGFR1), angiogenesis (HIPK2, CASP8), extracellular matrix organization (VWA1), and apoptosis (BBC3, HIPK2, KLF11, PSME3, MSFD10, TOP2A, MLH1, CASP8, PDIA3, XAF1) when comparing untreated chronic wounds to chronic wounds treated with DSS, with similar expression levels compared to untreated acute wounds. Chronic wounds treated with debridement followed by DSS resemble untreated acute wounds at a genomic level. These novel findings, albeit with limited clinical specimen numbers, strengthen the recommendation to transform chronic into acute wounds prior to application of DSS.